PTP1B negatively regulates nitric oxide-mediated Pseudomonas aeruginosa killing by neutrophils. - Lei Yue; Min Yan; Michel L Tremblay; Tong-Jun Lin; Hua Li; Ting Yang; Xia Song; Tianhong Xie; Zhongping Xie (PLoS ONE, 2019)
Neutrophils play a critical role in host defense against Pseudomonas aeruginosa infection. Mechanisms underlying the negative regulation of neutrophil function in bacterial clearance remain incompletely defined. Here, we demonstrate that protein tyrosine phosphatase-1B (PTP1B) is a negative regulator of P. aeruginosa clearance by neutrophils. PTP1B-deficient neutrophils display greatly enhanced bacterial phagocytosis and killing, which are accompanied by increased Toll-like receptor 4 (TLR4) signaling activation and nitric oxide (NO) production following P. aeruginosa infection. Interestingly, PTP1B deficiency mainly upregulates the production of IL-6 and IFN-β, leads to enhanced TLR4-dependent STAT1 activation and iNOS expression by neutrophils following P. aeruginosa infection. Further studies reveal that PTP1B and STAT1 are physically associated. These findings demonstrate a negative regulatory mechanism in neutrophil underlying the elimination of P. aeruginosa infection though a PTP1B-STAT1 interaction.